IMPLEMENTASI MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PRAKTIKUM LAS SMAW SISWA SMK - Muhammad Iqbal; Irzal Irzal; Purwantono Purwantono; Bulkia Rahim (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2026)
ABSTRACT The learning outcomes of Grade XI students of the Welding Engineering Department at SMK Negeri 2 Payakumbuh in the SMAW Electric Arc Welding practicum for the 1G position competency were still low, with 19 out of 28 students (68%) failing to achieve the Minimum Mastery Criterion (KKM) of 75. This problem was presumed to be caused by teacher-centered conventional learning, which made students passive and less capable of independently identifying and solving technical problems. This study aimed to implement the Discovery Learning model to improve students’ learning outcomes in both cognitive and psychomotor aspects in the 1G flat-position welding practicum. This study employed a Classroom Action Research design based on the John Elliot model, conducted in two cycles, each consisting of planning, action, observation, and reflection stages, involving 28 students as research subjects. Data were collected using knowledge tests and project assessment sheets that had been tested for validity and reliability, then analyzed descriptively using quantitative methods. The results showed a gradual improvement in students’ learning outcomes. Classical mastery in the cognitive aspect increased from 28.6% in the pre-cycle to 53.6% in Cycle I and reached 89.3% in Cycle II. In addition, the average psychomotor learning outcomes improved from 71.3 in Cycle I to 82.1 in Cycle II. Students’ final average score also increased from 73.98 in Cycle I to 81.8 in Cycle II. Therefore, the implementation of the Discovery Learning model was proven effective in improving students’ learning outcomes in the SMAW 1G flat-position welding practicum, both in cognitive and psychomotor aspects, and successfully exceeded the research success indicator of 75%. ABSTRAK Hasil belajar siswa kelas XI Teknik Pengelasan SMK Negeri 2 Payakumbuh pada praktikum Las Busur Listrik SMAW kompetensi posisi 1G masih rendah, dengan 19 dari 28 siswa (68%) belum mencapai Kriteria Ketuntasan Minimal (KKM) sebesar 75. Permasalahan tersebut diduga disebabkan oleh pembelajaran yang masih berpusat pada guru sehingga siswa cenderung pasif dan kurang mampu mengidentifikasi serta memecahkan masalah teknis secara mandiri. Penelitian ini bertujuan menerapkan model pembelajaran Discovery Learning untuk meningkatkan hasil belajar siswa pada aspek pengetahuan dan keterampilan dalam praktikum las posisi 1G bawah tangan. Penelitian ini merupakan Penelitian Tindakan Kelas (Classroom Action Research) model John Elliot yang dilaksanakan dalam dua siklus, masing-masing terdiri atas tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi, dengan subjek penelitian sebanyak 28 siswa. Data dikumpulkan menggunakan tes pengetahuan dan lembar penilaian proyek yang telah diuji validitas dan reliabilitasnya, kemudian dianalisis secara deskriptif kuantitatif. Hasil penelitian menunjukkan adanya peningkatan hasil belajar siswa secara bertahap. Ketuntasan klasikal aspek pengetahuan meningkat dari 28,6% pada pra siklus menjadi 53,6% pada Siklus I dan mencapai 89,3% pada Siklus II. Selain itu, rata-rata hasil belajar keterampilan meningkat dari 71,3 pada Siklus I menjadi 82,1 pada Siklus II. Nilai akhir siswa juga meningkat dari rata-rata 73,98 pada Siklus I menjadi 81,8 pada Siklus II. Dengan demikian, penerapan model Discovery Learning efektif meningkatkan hasil belajar siswa pada praktikum las SMAW posisi 1G bawah tangan, baik pada aspek pengetahuan maupun keterampilan, serta mampu melampaui indikator keberhasilan penelitian sebesar 75%.